Application Of Differentiated Learning Model In Islamic Religious Education Subjects (Case Study At Sekolah Terakan Pertamadan Negeri 1 Tangen Sragen) - Milani, Oki; Suhadi, Suhadi; Ulfah, Yetty Faridatul (UMSU, 2024)
This research aims to describe students' learning characteristics based on aspects of Islamic religious education subjects as well as describe the application of differentiated learning at Negeri 1 Tangen Sragen Middle School. The research method used is qualitative with a data collection process through interviews, observation and case studies with the application of learning. The data analysis technique used is triangulation by collecting information from interviews and observations. Then it is compared with previous research and expert opinions to draw valid conclusions. Differentiated learning outcomes give students the freedom to determine content that shows their understanding, skills and knowledge and express it in various products appropriate to their level of mastery. And there was an increase in learning outcomes after conducting a case study with the application of differentiated learning in Islamic Religious Education subjects. So it can be concluded from the results of this research that the application of differentiated learning can improve student learning outcomes at Tangen Sragen Junior High School (SMP).